1996
DOI: 10.1103/physrevb.53.14834
|View full text |Cite
|
Sign up to set email alerts
|

Second-order phase transition in crystals with long-range correlated quenched defects

Abstract: We consider the phase transition in a ferromagnet with line defects that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 22 publications
4
26
0
Order By: Relevance
“…On the other hand, many experimental contributions in the last two decades posed interesting questions about criteria of relevance, supplying results that challenge predictions made by previous theoretical works. Amongst all, those on the superfluid transition of 4 He in light aerogels are rather intriguing [6][7][8][9][10][11]. Changes of critical exponents for the so called λ-transition, when superfluid 4 He is confined in aerogel pores, were reported repeatedly from late 80's through late 90's, with almost the same question left open: do these results violate Harris and/or other relevance criteria?…”
Section: Harris Criterion In Brief: Original and Extendedmentioning
confidence: 87%
See 4 more Smart Citations
“…On the other hand, many experimental contributions in the last two decades posed interesting questions about criteria of relevance, supplying results that challenge predictions made by previous theoretical works. Amongst all, those on the superfluid transition of 4 He in light aerogels are rather intriguing [6][7][8][9][10][11]. Changes of critical exponents for the so called λ-transition, when superfluid 4 He is confined in aerogel pores, were reported repeatedly from late 80's through late 90's, with almost the same question left open: do these results violate Harris and/or other relevance criteria?…”
Section: Harris Criterion In Brief: Original and Extendedmentioning
confidence: 87%
“…The challenge to theory comes in the case of 4 He confined in silica aerogels (AE) and xerogels (XE), where authors observed ζ AE 0.81 and ζ XE 0.89, respectively, larger than the bulk exponent. After the WH model, these results suggest that LRC distributions of defects should be present within AE and XE.…”
Section: Phase Transitions In Aerogels: Experimentsmentioning
confidence: 99%
See 3 more Smart Citations